On double phase Kirchhoff problems with singular nonlinearity - Arora R.; Fiscella A.; Mukherjee T.; Winkert P. (My University, 2025)
In this paper, we study multiplicity results for double phase problems of Kirchhoff type with right-hand sides that include a parametric singular term and a nonlinear term of subcritical growth. Under very general assumptions on the data, we prove the existence of at least two weak solutions that have different energy sign. Our treatment is based on the fibering method in form of the Nehari manifold. We point out that we cover both the nondegenerate as well as the degenerate Kirchhoff case in our setting. © 2023 the author(s), published by De Gruyter.